Habitat suitability and niche interaction between the invasive snail Achatina fulica and its biocontrol flatworm Platydemus manokwari in Southeast Asia - Yu, Britney Ann; Cadiz, Geofe; Flores, Mary Joyce; Edullantes, Brisneve (BIODIVERS - BIOTROP Science Magazine, 2024)
Bioinvasions are increasingly altering community structures around the world, especially with the changing climate. In invaded areas, biocontrol agents are introduced to regulate the invasive species. However, without thorough evaluation, these agents can proliferate and threaten other organisms. We assessed the niche dynamics between invasive Achatina fulica (Giant African Snail) and its biocontrol agent, the Platydemus manokwari (New Guinea Flatworm), in Southeast Asia. Species occurrence and environmental data were used to model the habitat suitability of both species in the present and future climate scenarios using ecological niche modeling with the MaxEnt algorithm. These models predicted 25.9% and 42.0% of the current conditions to be suitable and 73.8% and 57.8% to be unsuitable for A. fulica and P. manokwari, respectively. There was a predicted steady increase in suitable areas and a gradual decrease in A. fulica’s unsuitable areas as the carbon emissions are predicted to increase. Moderate to high niche overlap of 61.2% to 83.4% was expected between the species under different climate scenarios. Predicting the suitable areas for invasive species and their niche interaction with other species in future scenarios will aid in identifying vulnerable areas for conservation.